The importance of immune evasion in the pathogenesis of rabies virus: Veterinary Science Award Winner’s (No.116) Commemorative Review - ITO, Naoto (J Vet Med Sci, 2016)
Rabies is a zoonotic disease caused by the Lyssavirus rabies virus (RABV) that can infect most mammals, including humans, where it has a case-fatality rate of almost 100%. Although preventable by vaccination, rabies causes c. 59,000 human fatalities every year worldwide. Thus, there exists an urgent need to establish an effective therapy and/or improve dissemination of vaccines for humans and animals. These outcomes require greater understanding of the mechanisms of RABV pathogenesis to identify new molecular targets for the development of therapeutics and/or live vaccines with high levels of safety. Importantly, a number of studies in recent years have indicated that RABV specifically suppresses host immunity through diverse mechanisms and that this is a key process in pathogenicity. Here, we review current understanding of immune modulation by RABV, with an emphasis on its significance to pathogenicity and the potential exploitation of this knowledge to develop new vaccines and antivirals.